Trust in Automated Writing Evaluation (AWE): Multiple case study on feedback engagement and literacy - Drajati, Nur Arifah; Handayani, Anis (UPT Bahasa Universitas Tanjungpura, 2024)
Artificial Intelligence (AI) for educational purposes has recently been a research interest. Specifically for academic writing, AI-based feedback, often called automated writing evaluation (AWE), is an essential aspect to support students